A questão russa para Marx e Engels - Del Roio, Marcos [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
O artigo aborda a evolução do pensamento de Marx e Engels sobre a Rússia dos czares, particularmente no que tange a política internacional e o papel da comuna agrária dentro da crise dessa formação social. Procura também perceber as diferenças de concepção presentes entre os fundadores do comunismo crítico.

This article approaches the evolution of Marx and Engels’ thoughts about the Russia of the czars, particularly in what they refer to the international politics and the role of the agrarian comuna in its own social development. It also tries to show the concept differences among the founders of the critical communism.
The Russian issue for Marx and Engels
Keywords: Rússia; Marxism; Rural comuna; Capitalism; East and West; Marxismo; Comuna rural; Capitalismo; Oriente e Ocidente